The Effect of Lemon Aromatherapy on Reducing Emesis Gravidarum in Pregnant Women in the First Trimester at TPMB (Midwife Independent Practice) in the Cempaka Health Center, Cianjur Regency, Indonesia - Deka Friska (HM Publisher, 2023)
Lemon aromatherapy can be used to create a calmer environment and reduce the tension that pregnant women may feel. Lemon aromatherapy can also be used as part of a relaxation routine. Smelling the scent of lemon while resting or meditating may help pregnant women feel calmer and more relaxed. This study aimed to determine the effect of lemon aromatherapy on reducing emesis gravidarum in trimester pregnant women I at TPMB (Midwife Independent Practice) in the Cempaka Health Center, Cianjur Regency, Indonesia. This study is experimental research with a one-group pre-post-test approach and uses primary data, namely measuring the degree of nausea and vomiting of research respondents. A total of 30 research subjects took part in this study. This study shows that lemon aromatherapy intervention is effective in reducing the degree of nausea. There was a decrease in the degree of nausea after giving lemon aromatherapy, and it was stated to be statistically different, p<0.05. In conclusion, there is an effect of lemon aromatherapy on reducing emesis gravidarum in trimester pregnant women I at TPMB (Midwife Independent Practice) in the Cempaka Health Center, Cianjur Regency, Indonesia.